Median effective volume of 0.2% ropivacaine for ultrasound-guided supraclavicular brachial plexus block in children aged 1–6 years: a prospective dose-finding study - Liu, Ling; Yang, Fei; Gao, Wen; Li, Shangyingying; Tian, Yaqiong; Yang, Li; Tu, Shengfen (Frontiers in Pediatrics, 2023)
Abstract: Objective: To determine the median effective volume (EV50) of 0.2% ropivacaine for ultrasound-guided supraclavicular brachial plexus block (SC-BPB) in children aged 1-6 years. Methods: Children aged from 1 to 6 years with an American Society of Anaesthesiologists (ASA) physical status I-II who were scheduled for unilateral upper extremity surgery at the Children’s Hospital of Chongqing Medical University were recruited. All patients underwent surgery under general anaesthesia combined with brachial plexus block. SC-BPB was guided by ultrasound after anaesthesia induction, and 0.2% ropivacaine was given after localization. In the study, we used Dixon's up-and-down approach with an initial dose of 0.50 mL/kg. Considering the effect of the previous block, a successful or failed block could produce a 0.05 mL/kg decrement or increment in volume, correspondingly. The experiment was stopped when there were 7 inflection points. Using isotonic regression and bootstrapping algorithms, the EV50, the 95% effective volume (EV95) and the 95% confidence interval (CI) were calculated. The patients’ general information, postoperative pain scores, and adverse events were also recorded. Results: Twenty-seven patients were involved in this study. The EV50 of 0.2% ropivacaine was 0.150 mL/kg (95% CI, 0.131 to 0.169 mL/kg) and the EV95 (secondary metric) was 0.195 mL/kg (95% CI, 0.188 to 0.197 mL/kg). No adverse events occurred during the research study. Conclusions: For ultrasound-guided SC-BPB in children aged 1-6 years undergoing unilateral upper extremity surgery, the EV50 of 0.2% ropivacaine was 0.150 mL/kg (95% CI, 0.131 to 0.169 mL/kg).